Effects of Exercise on Mitochondrial Content and Function in Aging Human Skeletal Muscle - Menshikova, Elizabeth V. (2006)
Skeletal muscle mitochondria are implicated with age-related loss of function and insulin resistance. We examined the effects of exercise on skeletal muscle mitochondria in older (age=67.3±0.6 yr) men (n=5) and women (n=3). Similar increases in (P<0.01) cardiolipin (88.2±9.0 to 130.6±7.5 μg/mU creatine kinase activity (CK)) and the total mitochondrial DNA (1264±170 to 1895±273 copies per diploid of nuclear genome) reflected increased mitochondria content. Succinate oxidase activity, complexes 2–4 of the electron transport chain (ETC), increased from 0.13±0.02 to 0.20±0.02 U/mU CK (P<0.01). This improvement was more pronounced (P<0.05) in SS (127±48%) compared to IMF (56±12%) mitochondria. NADH oxidase activity, representing total ETC activity, increased from 0.51±0.09 to 1.00±0.09 U/mU CK (P<0.01). In conclusion, exercise enhances mitochondria ETC activity in older human skeletal muscle, particularly in SS mitochondria, which is likely related to the concomitant increases in mitochondria biogenesis.